2017
DOI: 10.1021/acs.jced.6b00959
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Heat Capacity Measurements for R1234yf from 303 to 373 K and Pressures up to 12 MPa

Abstract: The isobaric heat capacity of 2,3,3,3-tetrafluoropropene (R1234yf) was studied in the compressed liquid and supercritical phases. A total of 154 experimental data were acquired for eight isotherms from 303.68 to 373.31 K in the pressure range of 1.5 to 12 MPa. The experimental values of the heat capacity were compared with the literature data. Additionally, the present data were correlated with an empirical equation. The published experimental data sets of thermophysical properties for R1234yf were also summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…Temperature T and pressure P range of the isobaric heat capacity c P measurements of R1234yf reported in this work (×); Liu et al (□); Gao et al (○); and Tanaka et al (Δ). Colors of the markers indicate the difference in c P compared to the EOS: green (<2%), blue (2–4%), and red (>4%).…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Temperature T and pressure P range of the isobaric heat capacity c P measurements of R1234yf reported in this work (×); Liu et al (□); Gao et al (○); and Tanaka et al (Δ). Colors of the markers indicate the difference in c P compared to the EOS: green (<2%), blue (2–4%), and red (>4%).…”
Section: Introductionsupporting
confidence: 55%
“…In particular, the measurements by Gao et al provide a very good agreement with the EOS as determined by the average absolute deviation (AAD) of just 0.3% . However, the existing c P measurements of R1234yf at supercritical conditions show a higher AAD of 3.2%, indicating a much larger divergence from the EOS …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The data of Gao et al (2014) also exhibit low scatter. On the other hand, the data of Tanaka et al (2010a), Liu et al (2017) and Lukawaski et al (2017), as well as the isochoric heat capacity data of Zhong et al (2018), deviate from the EOS by considerably larger amounts.…”
Section: Vapour-liquid Equilibriamentioning
confidence: 93%
“…Simultaneously, the deviation of these two terms to some extent might cancel out when applying CPA. 25 and the data of R1234yf (c, d) are from Liu et al 5 and Gao et al 6 To illustrate the observed trends better, calculation results of (residual isobaric heat capacity given in Equation ( 3)) with method 3 for R1234yf and R1233zd(E) are presented in Figure 3.…”
Section: (I)mentioning
confidence: 96%